The Experiments Study of Tight Gas Sandstone Permeability by Effective Stress and Temperature Coupling - Hao, Zhang; Xiangyi, Yi (Physical and Numerical Simulation of Geotechnical Engineering, 2017)
Reservoir physical properties of tight sandstone are extremely sensitive to stress. The stress sensitivity coefficient evaluation criteria have been selected to analysis the degree of the permeability sensitivity. Sandstone rock samples have been used to evaluate the stress and temperature sensitivity, the results shows that with the increase of effective stress, permeability of reservoir rocks decrease continuously. It shall be seen from the table that the stress sensitivity coefficient range of the rock sample is from 0.32 to 0.62, it generally belongs to medium permeability stress sensitivity, and rising temperature is equivalent to adding stress, under the joint action of high effective stress and rising temperature, seepage space in reservoirs tends to become smaller.